A inserção das mulheres na engenharia civil: estudo de caso na UFERSA Campus Caraúbas/RN - Cortez, Samya Vanessa (Universidade Federal Rural do Semi-Árido, 2018)
This study presents an investigation and reflections on women‟s integration into the engineering course, designing their profile when getting into UFERSA (Campus Caraúbas). It is also presented a characterization of women‟s integration into the job market and how the institution analyzes and evaluates their advance within the field of civil engineering. The method used as the basis of this study was the informative reading, altogether with the bibliographical review and the analysis of the data provided by UFERSA‟s Divisão de Registro Escolar (DRE – Academic Records Division) at Campus Caraúbas. In order to collect the data, the students answered a structured questionnaire that aimed to understand students‟ specific knowledge. The data analyzed revealed that although these women had access to formal education only recently, they represent now the majority of students getting into undergraduate courses. However, the number of women in exact sciences courses is still inferior to the number of men enrolled at the same courses, such as Science and Technology and Civil Engineering. At UFERSA/Caraúbas there is still a gender disparity with the percentage of men being superior to the percentage of women enrolled at these courses. However, the number of women getting into Science and Technology and Civil Engineering courses have been increasing throughout the academic semesters and they are the ones that represent the lowest dropout percentage and also represent the greatest Civil Engineering undergraduate course completion rates. The institution has given the engineering degree to fifty students until the current semester and 54% of the new engineers are women. There is an evolving path ahead of us, leading to the empowerment of women who overcome many hurdles when choosing to become engineers.
Monografia
Keywords: Mulher; Universidade; Campus Caraúbas; Engenharia; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA